Revitalization of Integrated Thematic Material to Improve the Learning Process - Afriani, Karmela (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
The aim of this research is to improve students' abilities in the learning process, especially in integrated thematic learning material in class IV. This research method is Research and Development (R&D). This development research procedure uses the ADDIE model. This research instrument is a validation questionnaire for material experts, media experts, language experts and practitioner experts and interview sheets for students and class teachers. The results of this research are: (1) Revitalization of integrated thematic material to improve the learning process for class IV with theme 2